Toward Food Sovereignty: Transformative Agroecology and Participatory Action Research With Coffee Smallholder Cooperatives in Mexico and Nicaragua - Guzmán Luna, Alejandra; Bacon, Christopher M.; Méndez, V. Ernesto; Flores Gómez, María Eugenia; Anderzén, Janica; Mier y Terán Giménez Cacho, Mateo; Hernández Jonapá, Rigoberto; Rivas, Misael; Duarte Canales, Henry Alberto; Benavides González, Álvaro Nicolás (Frontiers in Sustainable Food Systems, 2022)
The challenges that coffee smallholder livelihoods face suggest the need to move beyond incremental changes in production. Transformative agroecology offers a potential approach to guide systemic change to achieve food sovereignty among coffee smallholders and cooperatives. This work aims to understand the extent to which diversification practices among coffee smallholders can contribute to a transformative agroecology, and to what extent, participatory action research (PAR) projects may support related transformative processes. The PAR projects described in this paper took place over 3 years with participants associated with two smallholder cooperatives in Mexico, and Nicaragua. After establishing long-term partnerships among cooperatives and universities, we used a PAR approach to guide a mixed methods study that included 338 household surveys, 96 interviews, 44 focus group discussions, and participant observation during farmer-to-farmers exchanges. We found that, although coffee-producing households in both study sites report several diversification activities, more than 50% still face some period of food scarcity each year. In our reflections with farmers and staff from the participating cooperatives, that are also included as co-authors in this study, we conclude that coffee smallholders and cooperatives in both locations are in the early stages of developing a transformative agroecology, as a path toward food sovereignty. Several leverage points to achieve this include land access, native seed conservation, cultural attachment to certain diversification practices, and traditional diets. Some of the more significant challenges to advancing a more transformative agroecology are the prioritization of coffee as a crop (i.e., coffee specialization), and dependency on coffee income. Our PAR project also aimed to contribute to achieving change in the prevailing system through 1) capacity building with community facilitators/promoters, 2) co-creation of questions and knowledge relevant to the strategic planning by coffee cooperatives, 3) sharing farmer-to-farmer pedagogies across territories, and 4) the co-production of popular education material. We conclude that diversification remains an important agroecological strategy for smallholder commodity producers, as a way of achieving food sovereignty. Most of all, we find that achieving diversification is not a linear process, as there are many trade-offs, feedback loops, obstacles and opportunities that should be considered through long-term and collective approaches.